The Creativity of the Hand. Issue 2 (3rd July 2019) - Gebauer, Gunter
ABSTRACT: In this article I argue that, with the liberation of the hand from the tasks of locomotion in human evolution, unconscious use of the hands begins to create cultural forms. The first feature of the hands is its openness to the world. The second feature is its mediation between things and the body of which it is a part. The third feature is its self-referentiality . By touching, by giving form to a material, by gestures, and by establishing symbolic order in the given world, the actions of the hand develop important preconditions for language, aesthetic forms, and social order. The hand itself assumes the most diverse shapes and gives different shapes to the objects around it. Touching and pointing produce the certainty that the indicated object exists, insofar as it is produced as object-for-the-hand . Its doubling in the use of the hand re-creates the object in a symbolic medium. This mimetic re-creation of the world is the main characteristic of the creativity of hand use. The two-sided plasticity of the hands divides the social universe into right and left halves, classified according to right-handed and left-handed values. The hand's actual acquisition of this capacity is the result of a social process . In coordination with our visual sense, the use of the hands leads both to the making of objects and to the construction of worlds of subjective feelings. Both achievements are often ascribed to language. But the functions considered as most fundamental to language first take shape in the unconscious use of our hands.